Recent Progress in the Synthesis of Drugs and Bioactive Molecules Incorporating Nitro(het)arene Core - Maxim Bastrakov; Alexey Starosotnikov (MDPI AG, 2022)
Aromatic nitro compounds play a unique role in the synthesis of drugs and pharmaceutically oriented molecules. This field of organic chemistry continues to be in demand and relevant. A significant number of papers are published annually on new general methods for the synthesis of nitrodrugs and related biomolecules. This review is an analysis of the literature on methods for the synthesis of both new and already-known aromatic and heteroaromatic nitrodrugs covering the period from 2010 to the present.